KEPATUHAN DITINJAU DARI KEPRIBADIAN EKSTROVERT-INTROVERT - Nanda Purwanti; Abdul Amin (Ilmu Psikologi Universitas Yudharta Pasuruan)
As human beings living in society with rules governing values and social norms prevailing in it, human beings have a set of rules to be followed in connection with the receipt he was in a community. If he does not comply with these rules and regulations, it will be considered abnormal, strange, wayward and deviant. Every individual has different characteristics, which are the characteristics that distinguish between individuals with one another. Diversity is because every individual has a different personality. So that behavior that appears to influence the social that occur in their environment are often different. The results showed that the hypothesis that states there is a difference between extroverted personality compliance with accepted introvert. Analysis of the data using a t-test between groups and the results obtained t - among at 13,339. ttable 5% and amounted to 1,980 ttable 1% at 2,617. So it can be stated very significant. So, there are differences in average adherence among people with extrovert or introvert personality.